Pectus excavatum in two littermate dogs - Rahal, Sheila C. [UNESP]; Morishin Filho, Milton M. [UNESP]; Hatschbach, Eduardo [UNESP]; Machado, Vânia Maria V. [UNESP]; Aptekmann, Karina P. [UNESP]; Corrêa, Thais P. [UNESP] (My University, 2008)
One male and 1 female, 8-week-old, schnauzer littermates were presented with moderate and mild pectus excavatum, respectively. External application of a coaptation splint to the ventral aspect of the thorax was used for correction of the sternal deformity in the male; conservative treatment was used in the female.